On quasiperiodic oscillations of a nonlinear dynamic system of Liapunov type with time lag - Can, Le Xuan (Vietnam Journal of Mechanics, 1998)
The paper is concerned with the investigation of the quasiperiodic oscillations of a nonlinear dynamic system of Liapunov type with time lag. The following results are obtained:- The necessary and sufficient conditions for the existence of the quasiperiodic solution describing the oscillating processes.- The approximate quasiperiodic solution in the power series.- The quasiperiodic oscillations of a nonlinear dynamic system of Duffing type with the quasiperiodic perturbations.